تصور مقترح لتصميم معجم مصطلحات فقه الـمناكحات لطلاب قسم الشريعة الناطقيـن بغيـر العربية: A Proposal to Design a Dictionary of Munakhat Jurisprudence Terms for Non-Arabic Speaking Students of The Sharia - Maryam Abdul Rahman; Kamariah Abdul Rahman (RABBANICA - Journal of Revealed Knowledge, 2025)
This study is a serious step towards designing a specialized dictionary of Fiqh al-Munakahat (Islamic family law) terms, which is important in supporting the education for the non-Arabic-speaking Sharia students. The study seeks to develop a conceptual framework in building glossary, which includes simplified explanations of jurisprudential terms along with translations into the most commonly used languages among students, supported by practical Sharia-based examples for each term. The proposed approach organizes terms according to jurisprudential categories, such as marriage, divorce, and alimony, and is designed to provide easy access to information, with guidance for effective glossary use. This initiative addresses the lack of suitable resources that provide non-Arabic-speaking students with a clear and structured understanding of this area of Islamic law, highlighting the importance of this study in offering a dependable and well-organized reference in the field. Additionally, the study aims to offer structured solutions to the challenges these students face in comprehending Fiqh al-Munakahat terms, drawing on previous research and modern teaching methods. تُعدّ هذه الدراسة خطوة جادّة نـحو تصميم معجم متخصص لـمصطلحات فقه الـمناكحات، وهو في غاية الأهـمية لدعم تعليم الشريعة الإسلامية للطلاب الناطقين بغير العربية. وتسعى هذه الدراسة إلى وضع تصور مقترح لأسس بناء هذا المعجم الذي يتضمن شرحًا مبسطًا للمصطلحات الفقهية مع تقديم ترجمات إلى اللغة الأكثر استخدامًا من قِبل الطلاب من خلال أدلة شرعية تطبيقية لكل مصطلح. كما يستند المنهج المقترح إلى تقسيم المصطلحات وفق الأبواب الفقهية مثل الزواج، والطلاق، والنفقة. وتصميمه وهيكلته بشكل يسهل الوصول إلى المعلومات، ويتضمن أيضًا توجيهات لاستخدام المعجم بشكل فعّال. يأتي ذلك استجابةً لمشكلة عدم توفر موارد ملائمة لفهم هذا الجانب من الشريعة الإسلامية بشكل واضح ومنهجي للطلاب الناطقين بغير العربية، مما يبرز أهمية هذه الدراسة في تقديم مرجع موثوق ومنظم في هذا المجال. كما تهدف الدراسة إلى تقديم حلول منهجية للمشكلات التي يواجهها هؤلاء الطلاب في استيعاب مصطلحات فقه الـمناكحات، مع الاستفادة من الدراسات السابقة والطرق التعليمية الحديثة.